Islam And Human Rights: A Case For Indonesian Muslim - Husin, Baharuddin; Ananda, Faisar; Rivai Zainal, Veithzal; Supriyatin (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to observe the compatibility of Indonesian Muslims to human rights practice in Indonesia and how they adapt to the realities amid presumption that Islam does not highlight rights in its core teaching. For that presumption, it could be noted that there are several cases which demonstrate clash-like encounter between Islam and human rights. This research involves qualitative methods which is operated through study of legal documents to obtain data. The result of this study shows that dispute-like in between Islam and human rights may be disentangled by introducing new approach of interpretation to legal verses of the very source of Quran to align with human rights. This study could suggest an alternative to decode Quranic sources and make them comparable to the matter of modern jurisdiction.